The effect of rifampin on the pharmacokinetics of sirolimus in healthy volunteers. Issue 1 (18th June 2013) - Tortorici, Michael A.; Matschke, Kyle; Korth‐Bradley, Joan M.; DiLea, Cliff; Lasseter, Kenneth C.
Abstract Sirolimus, metabolized primarily by intestinal and hepatic CYP3A4, is a substrate for P‐glycoprotein. CYP3A4 inducers would be expected to decrease sirolimus exposure. This open‐label, nonrandomized study investigated effects of CYP3A4 induction, by rifampin, on sirolimus pharmacokinetics. Healthy volunteers received sirolimus 20 mg on day 1. After washout period, multiple 600‐mg rifampin doses were administered daily for 14 days. On day 9, one 20‐mg sirolimus dose was administered after an overnight fast (≥10 hours). Whole blood samples for sirolimus collected for 144 hours after each dose were analyzed by liquid chromatography/tandem mass spectrometry. Pharmacokinetic parameters, assessed using noncompartmental methods, were compared using analysis of variance. Geometric mean ratios of Cmax and AUCinf were 29% (90% CI: 26, 32%) and 18% (90% CI: 16, 21%), respectively, with rifampin co‐administration versus sirolimus alone. Corresponding decreases in Cmax and AUC were 71% and 82%, respectively, which would likely cause trough concentrations to fall below the recommended therapeutic range. Mean CL/F increased approximately fivefold with rifampin versus sirolimus alone. Co‐administering sirolimus and potent CYP3A inducers is not recommended. If co‐administration is necessary, dose adjustment and concentration monitoring should be conducted.